Carbapenem-resistant Enterobacterales bacteriuria and subsequent bacteremia: A population-based study. (10th August 2021) - Howard-Anderson, Jessica R.; Bower, Chris W.; Smith, Gillian; Sexton, Mary Elizabeth; Farley, Monica M.; Satola, Sarah W.; Jacob, Jesse T.
Abstract: Objective: To describe the epidemiology of carbapenem-resistant Enterobacterales (CRE) bacteriuria and to determine whether urinary catheters increase the risk of subsequent CRE bacteremia. Design: Using active population- and laboratory-based surveillance we described a cohort of patients with incident CRE bacteriuria and identified risk factors for developing CRE bacteremia within 1 year. Setting: The study was conducted among the 8 counties of Georgia Health District 3 (HD3) in Atlanta, Georgia. Patients: Residents of HD3 with CRE first identified in urine between 2012 and 2017. Results: We identified 464 patients with CRE bacteriuria (mean yearly incidence, 1.96 cases per 100, 000 population). Of 425 with chart review, most had a urinary catheter (56%), and many resided in long-term care facilities (48%), had a Charlson comorbidity index >3 (38%) or a decubitus ulcer (37%). 21 patients (5%) developed CRE bacteremia with the same organism within 1 year. Risk factors for subsequent bacteremia included presence of a urinary catheter (odds ratio [OR], 8.0; 95% confidence interval [CI], 1.8–34.9), central venous catheter (OR, 4.3; 95% CI, 1.7–10.6) or another indwelling device (OR, 4.3; 95% CI, 1.6–11.4), urine culture obtained as an inpatient (OR, 5.7; 95% CI, 1.3–25.9), and being in the ICU in the week prior to urine culture (OR, 2.9; 95% CI, 1.1–7.8). In a multivariable analysis, urinary catheter increased the risk of CRE bacteremia (OR, 5.3; 95% CI, 1.2–23.6). Conclusions: In patients with CRE bacteriuria, urinary catheters increase the risk of CRE bacteremia. Future interventions should aim to reduce inappropriate insertion and early removal of urinary catheters.